Investigation of negative effects of rice husk silica on komatsuna growth using three experiments - Le Van Chieu; Masafumi Tateda; Ryoko Sekifuji (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aims to evaluate the potential negative effects of rice husk as a source of fertilizer on plant growth. Method Growth tests were conducted on komatsuna (Brassica rapa var. perviridis) using three types of experiment. A pot experiment was conducted to compare different fertilizers on an individual basis. A second pot experiment was conducted to compare different mixtures of fertilizers. Finally, a field experiment was performed to determine the effects of the application of different quantities of silica. Results The results showed that komatsuna grew better with the application of silica mixed with fertilizer, and that there was an optimal quantity of silica to be used, when used on its own. It was found that, in all cases, the silica in the rice husk ash did not have any measurable negative effects on the growth of the komatsuna. Conclusion We, therefore, conclude that rice husk silica can undoubtedly be used for plant cultivation.